Use of microsatellite‐based paternity assignment to establish where Corn Crake Crex crex chicks are at risk from mechanized mowing. (18th March 2019) - Green, Rhys E.; Brekke, Patricia; Ward, Hannah; Slaymaker, Matt; van der Velde, Marco; Komdeur, Jan; Dugdale, Hannah L.
Abstract : We used microsatellite DNA to assign probable parentage of young Corn Crakes to adult males and females and used these assignments to estimate the distribution of distances between broods of chicks and juveniles and the night‐time singing place of the father at the time of initiation of the clutch. Estimated distances for broods of young chicks were in accord with those estimated previously by radiotracking, but distances were greater for older unfledged independent chicks not studied previously. Our results indicate that modifications of the timing and method of mowing to reduce losses of nests and chicks should be implemented inside an area within about 500 m of the singing places of male Corn Crakes, rather than the 250 m previously considered to be safe.